SURVEI DAN PEMETAAN STATUS HARA TEMBAGA DAN BORON PERKEBUNAN KELAPA SAWIT RAKYAT HUTABAYU RAJA - Daniel Stepanus; Supriadi Supriadi; Sarifuddin Sarifuddin (Jurnal Agroekoteknologi, 2013)
ABSTRACTThe purpose of this study is to know the status of copper (Cu) and Boron (B)at People Palam OilPalm Plantation at Hutabayu Raja Subdistrict, Simalungun District. The result of this study showedthat the status of the two micronutrients are :copper deficient area is about 22.7% (71 Ha) andadequate soil contains Cu is about 77.3% (239 Ha) and the soil content of B is deficient within theresearch are.